Evaluating Cognitive Level of Final Semester Examination Questions Based on Bloom’s Revised Taxonomy - Pirman Ginting; Yenni Hasnah; Selamat Husni Hasibuan; Ismail Hanif Batubara (STAI Hubbulwathan Duri, 2021)
This paper addresses the question of how cognitive levels covering high, middle, and low order thinking skills are delineated in the questions seen from Bloom’s revised taxonomic framework and stimulus. To answer this question, the final-term examination questions from five faculty courses were analyzed through document analysis. The documented examination questions are categorized and reviewed based on cognitive levels referring to revised Bloom’s taxonomy. The questions are also construed based on the stimulus in each question. The results report that the cognitive level of tests is not wholly based on higher-order thinking skills. Of the five courses, only one follows the higher-order thinking skills-based question-writing system, and none of the items refers to middle-order thinking skills. Thus, the cognitive level on the test instruments has not led to an increase in thinking skills or is still at a low level of thinking.